2000
DOI: 10.1016/s0960-9822(00)00579-0
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways and cell mechanics involved in wound closure by epithelial cell sheets

Abstract: Wounds in MDCK cell sheets do not close by purse-string contraction but by a crawling behavior involving Rac, phosphoinositides and active movement of multiple rows of cells. This finding suggests a new distributed mode of signaling and movement that, nevertheless, resembles individual cell motility. Although Rho and Cdc42 activities are not required for closure, they have a role in determining the regularity of closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
268
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(292 citation statements)
references
References 30 publications
22
268
1
1
Order By: Relevance
“…Namely, Taniuchi et al (2005) showed that a pancreatic cancer cell line, transfected with wild-type P-cadherin, migrated faster than the cells without this molecule. Epithelial cell migration requires the coordination of three basic cellular processes: actin cytoskeleton reorganization, matrix adhesion and matrix re-modelling (Lauffenburger and Horwitz, 1996;Fenteany et al, 2000). In this present study, we also show, by time-lapse microscopy and actin phalloidin staining, that P-cadherin is able to induce phenotypic changes involving alterations in cell polarity and leading edge morphology, formation of membrane protrusions, as well as, increase of their cytoplasmic area, which usually is characteristic from cells with a motile behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, Taniuchi et al (2005) showed that a pancreatic cancer cell line, transfected with wild-type P-cadherin, migrated faster than the cells without this molecule. Epithelial cell migration requires the coordination of three basic cellular processes: actin cytoskeleton reorganization, matrix adhesion and matrix re-modelling (Lauffenburger and Horwitz, 1996;Fenteany et al, 2000). In this present study, we also show, by time-lapse microscopy and actin phalloidin staining, that P-cadherin is able to induce phenotypic changes involving alterations in cell polarity and leading edge morphology, formation of membrane protrusions, as well as, increase of their cytoplasmic area, which usually is characteristic from cells with a motile behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…There are some significant distinctions of size, speed, and degree of cellularization that make closure of the Xenopus cleavage furrow an interesting process to investigate. For example, compared with in vivo wound closure models such as corneal epithelium (Matsuda et al, 1985) or Xenopus tadpole tail (Radice, 1980), in which free margins typically advance in the range of 2-10 m/min, respectively, or in vitro models such as monolayered MDCK cells, which may be 10 -100ϫ slower yet (Fenteany et al, 2000), closure of the Xenopus embryo cleavage furrow proceeds with extreme rapidity. Zippering by the first cleavage furrow closes a 1-mm opening in approximately 15 min.…”
Section: Discussionmentioning
confidence: 99%
“…Differences among cell types, coupled with the participation of Cdc42 in cell-cell adhesion [38], further complicate the issue. For example, Cdc42 is not required for wound closure by Madin-Darby canine kidney (MDCK) cells [39]. In addition to inducing the formation of filopodia, Cdc42 regulates cell polarity during movement [40].…”
Section: Discussionmentioning
confidence: 99%